ANALYSIS OF EFFICIENT PORTFOLIO FORMATION USING THE MARKOWITZ MODEL IN PALM OIL COMPANIES IN BEI FOR THE PERIOD 2020-2022 - Dinda Ayu S. W; Rachelia Putri N. A, Istiono (Adisam Publisher, 2024)
This study aims to see the expected return of each portfolio combination and the risk associated with each portfolio combination and determine which Investment portfolio combination can be an efficient investment. The data used in this study is stock closing price data for the period November 2020 to October 2022 (2 years). The sample of this study used 5 palm oil companies listed on the IDX. Based on the results of the calculations that have been carried out, there are 5 stock portfolios with different proportions of funds. Efficient portfolios based on the Markowitz model are: Portfolio 4 with a combination of funds PSGO (35%), SGRO (20%), SIMP (10%), CSRA (20%), and ANJT (15%) because it produces the highest return of 0.024 with a risk of 0.074. But if investors do not like risk, then investors choose portfolio 5 with a combination of PSGO (5%), SGRO (60%), SIMP (20%), CSRA (10%), and ANJT (5%) funds because it produces the lowest risk of 0.061 with a return of 0.020.